Central giant cell granuloma of the anterior maxilla - Sholapurkar Amar; Pai Keerthilatha; Ahsan Auswaf (Wolters Kluwer Medknow Publications, 2008)
Central giant cell granuloma (CGCG) formerly called giant cell reparative granuloma is a non-neoplastic proliferative lesion of unknown etiology. It occurs most commonly in the mandible. The case reported here resembled a wide variety of conditions that led to a misdiagnosis both on clinical and radiographic examination but was histopathologically diagnosed as CGCG. We describe a case of central giant cell granuloma arising from the anterior maxilla to highlight to the general dental practitioner the importance of histopathology in the diagnosis of this enigmatic lesion.